Managing meetings in organizations - Meinecke, Annika L.; Allen, Joseph A., 1981-; Lehmann-Willenbrock, Nale, 1982- (Research on managing groups and teams, 2020)
Groups and teams are the backbone of modern organizations and the driving force behind innovation. Employees come together to pool their efforts, join forces, develop creative ideas, and make decisions in one key social context: the workplace meeting. This volume presents novel perspectives and state-of-the art research insights into the management of meetings in the workplace. Managing Meetings in Organizations sheds light on key trends with regards to the changing nature of work and highlights how these trends map on to new challenges for managing effective meetings. The twelve chapters that compose this volume cover four overarching topics: conceptual foundations, the intersection of individual and team processes, diversity and gender, and leadership and strategy in and through meetings. The international team of contributors includes authors from industrial and organizational psychology, management, organizational behaviour, and evolutionary psychology. By establishing that meetings form a core interactional context for groups and teams in organizations, this book shows that finding ways to run effective meetings is more important than ever. Managing Meetings in Organizations appeals to researchers and academic scholars in industrial and organizational psychology, management, and organizational behaviour, as well as practitioners looking for evidence-based recommendations for managing workplace meetings.